Utility and clinical effectiveness of liquid biopsy-based DNA methylation testing in early tumor screening and diagnosis, emphasizing older adult populations: a systematic review and meta-analysis - Gao, Yujuan; Xu, Haoyu; Li, Juan; Li, Minli; Zhu, Desheng (Frontiers in Oncology, 2026)
BackgroundThe global aging population faces a disproportionate burden of lung cancer, creating an urgent need for minimally invasive screening methods. Liquid biopsy-based DNA methylation testing, particularly targeting the cysteine dioxygenase type 1 (CDO1) gene promoter, has emerged as a promising approach for early cancer detection. This study aims to systematically evaluate the diagnostic value of CDO1 promoter methylation in lung cancer using liquid biopsies.MethodsA comprehensive literature search was conducted across PubMed/MEDLINE, Embase, Web of Science, and Cochrane Library from inception to 28Th September, 2025. Studies reporting CDO1 promoter methylation in liquid biopsies (blood, urine, or sputum) for lung cancer detection with histological confirmation were included. Methodological quality was assessed using QUADAS-2. Bivariate random-effects models were used to calculate pooled sensitivity, specificity, diagnostic odds ratio (DOR), positive/negative likelihood ratios (PLR/NLR), and 95% confidence intervals.ResultsSeven studies involving 655 lung cancer cases and 402 controls were included. CDO1 methylation demonstrated pooled sensitivity of 0.72 and specificity of 0.89 for blood-based liquid biopsies, and 0.66 and 0.87 for non-blood specimens, respectively. The overall diagnostic odds ratio was 19.13 (95% CI: 13.53-26.84), with positive and negative likelihood ratios of 7.73 (95% CI: 5.77-10.35) and 0.32 (95% CI: 0.26-0.39). No significant heterogeneity was observed across studies (I² = 0% for all parameters). Subgroup analyses revealed consistent performance across different specimen types and geographic regions.ConclusionCDO1 promoter methylation detection in liquid biopsies shows robust diagnostic accuracy for lung cancer, with performance characteristics supporting its potential clinical utility, particularly for older populations who face barriers to conventional screening. The consistency across diverse specimen types and populations underscores its promise as a minimally invasive screening tool.